Perception of student and alumni of accounting department toward fraudulent practices - Ajeng Astari Ayuningtyas (The Indonesian Accounting Review, 2013)
Fraudulent practices are increasingly prevalent in our community, including amongstudents. These practices happen because of the pressure from their surrounding environment.When these practices are done by students without any adequate sanction,these may be perceived by them as normal and will eventually being a habit. The purposeof this research is to observe whether there is different perception of fraudulentpractices between students and alumni of accounting department at STIE PerbanasSurabaya. This research uses primary data collected using questionnaires. The respondentsare students who have finished taking course in Business Ethics and AccountingBehavior and alumni who have worked in Surabaya. There are 112 questionnairesprocessed, consisting of seventy questionnaires from students and fourty two questionnairesfrom alumni. The hypothesis is tested using independent sample t-test. Theresult of this research shows that there is no different in perception between accountingstudents and alumni regarding fraudulent practices. Both of them agree thatfraudulent practices occur because of motivation, opportunity and lack of integrity.